Whole‐genome resequencing reveals signature of local adaptation and divergence in wild soybean - Jiao Wang; Zhenbin Hu; Xiliang Liao; Zhiyu Wang; Wei Li; Peipei Zhang; Hao Cheng; Qing Wang; Javaid Akhter Bhat; Hui Wang; Biao Liu; Hengyou Zhang; et al. (Evolutionary Applications, 2022)
Abstract Global climate change has threatened world crop production and food security. Decoding the adaptive genetic basis of wild relatives provides an invaluable genomic resource for climate‐smart crop breedinG. Here, we performed whole‐genome sequencing of 185 diverse wild soybean (Glycine soja) accessions collected from three major agro‐ecological zones in China to parse the genomic basis of local adaptation in wild soybean. The population genomic diversity pattern exhibited clear agro‐ecological zone‐based population structure, and multiple environmental factors were observed to contribute to the genetic divergence. Demographic analysis shows that wild soybeans from the three ecological zones diverged about 1 × 105 years ago, and then the effective population sizes have undergone different degrees of expansions. Genome‐environment association identified multiple genes involved in the local adaptation, such as flowering time and temperature‐related genes. A locus containing two adjacent MADS‐box transcription factors on chromosome 19 was identified for multiple environmental factors, and it experienced positive selection that enables the adaptation to high‐latitude environment. This study provides insights into the genetic mechanism of ecological adaptation in wild soybean that may facilitate climate‐resilient soybean breeding.